O Faktum da razão como argumento crítico na teoria moral de Kant - Bicalho, Vanessa Brun (2013)
This research has as main purpose to analyze the validity from argument from Faktum of reason how possible founder of the moral law and freedom in Kant's practical philosophy. In order to explain the moral-practical domain in which conceptualized the argument from Faktum of reason, our text will demonstrate initially from the reading of the Critique of Pure Reason, the limits of theoretical reason by which, by the distinction of objects in general phenomenon and noumena, Kant founds both the speculative domain of reason as well, then the practical reason. The determination of the limits from the understanding´s faculty is crucial to establish the thematization of the freedom´s concept as a concept not only speculative (transcendental freedom), but also practical reason (practical freedom). Only so are presented the conditions to be thought of as not contradictory Nature and Freedom. Through the understanding of how theoretical reason (Verstand) knows, and the proper way to understand what pure reason (Vernunft) admits in favor from thinking of ideas that relate to the knowledge (ex., soul, God, and freedom), Kant developed the project of transcendental reason, the systematic point of view. The presence from the argument from Faktum of reason, a single fact admitted this as the reason (Vernunft) contrasted with the Kantian moral theory, developed and explained to the Groundwork from the Metaphysics of Morals. The argument of a Faktum at this reason, brought by the Critique of Practical Reason, caused a disturbance in the reception of Kant´s moral theory, giving breath to a debate on the possession, by reason, of the freedom´s concept. This new foundation argument was explained by Kant as an consciousness of immediately practical, awareness by itself and in itself guarantees the cogency of justification of possession from freedom, in our view, as the only critical argument can be provided by the faculty of pure practical reason. Unfavorable interpretations and receptions from Kant´s strategy of reasoning from freedom in Faktum of reason are discussed in this dissertation. Many current proposals to counteract the appearance of coherent Kant´s strategy brought by Critique of Practical Reason is shown attached to the previous movements of proof to demonstrate the freedom´s concept. In opposition to these proposals, which are a deconstruct component in the Kant´s argument of the perspective from critical-transcendental reason or systematic conformation, our text establishes a dialogue to elucidate the possible incongruities argumentative these interpretations, the themes of freedom (transcendental) and defense of Faktum as compatible arguments with the main transcendental perspective of reason, so kept in accordance with the project of reason from founding a Metaphysics of Morals.